Upregulated miRNAs on the TP53 and RB1 Binding Seedless Regions in High-Risk HPV-Associated Penile Cancer - da Silva, Jenilson; da Costa, Carla Cutrim; de Farias Ramos, Ingryd; Laus, Ana Carolina; Sussuchi, Luciane; Reis, Rui Manuel; Khayat, André Salim; Cavalli, Luciane Regina; Pereira, Silma Regina (Frontiers in Genetics, 2022)
Cancer development by the human papillomavirus (HPV) infection can occur through the canonical HPV/p53/RB1 pathway mediated by the E2/E6/E7 viral oncoproteins. During the transformation process, HPV inserts its genetic material into host Integration Sites (IS), affecting coding genes and miRNAs. In penile cancer (PeCa) there is limited data on the miRNAs that regulate mRNA targets associated with HPV, such as the TP53 and RB1 genes. Considering the high frequency of HPV infection in PeCa patients in Northeast Brazil, global miRNA expression profiling was performed in high-risk HPV-associated PeCa that presented with TP53 and RB1 mRNA downregulated expression. The miRNA expression profile of 22 PeCa tissue samples and five non-tumor penile tissues showed 507 differentially expressed miRNAs: 494 downregulated and 13 upregulated (let-7a-5p, miR-130a-3p, miR-142-3p, miR-15b-5p miR-16-5p, miR-200c-3p, miR-205-5p, miR-21-5p, miR-223-3p, miR-22-3p, miR-25-3p, miR-31-5p and miR-93-5p), of which 11 were identified to be in HPV16-IS and targeting TP53 and RB1 genes. A number of 131 and 490 miRNA binding sites were observed for TP53 and RB1, respectively, most of which were in seedless regions. These findings suggest that up-regulation of miRNA expression can directly repress TP53 and RB1 expression by their binding sites in the non-canonical seedless regions.